The Role of Cognition in Social Information Use for Breeding Site Selection: Experimental Evidence in a Wild Passerine Population - Morinay, Jennifer; Cauchard, Laure; Bize, Pierre; Doligez, Blandine (Frontiers in Ecology and Evolution, 2020)
In spatio-temporally variable environments, individuals are known to use information for making optimal decisions regarding where and when to breed. Optimal decision making can be complex when relying on multiple information sources with varying levels of reliability and accessibility. To deal with such complexity, different cognitive abilities such as learning and memory might enable individuals to optimally process and use these information. Yet, the link between information use and cognitive ability remains unexplored in natural populations. We investigated whether learning performance on a problem-solving task was related to the use of an experimentally manipulated source of social information for nest site selection in wild collared flycatchers (Ficedula albicollis). Collared flycatchers are known to use heterospecific information from their main competitors, the great tits (Parus major). Here, we created a local apparent preference by tits for an artificial nest site feature (a geometric symbol attached to nest boxes occupied by tits) and recorded whether flycatcher pairs chose to settle in nest boxes displaying the same feature as tits (i.e. copied tit apparent preference). Using a problem-solving task requiring opening a door temporarily blocking the nest box entrance, we then measured flycatchers’ learning performance during nestling rearing as the number of entrances required to solve the task and enter the nest box twice in a row below a given efficiency threshold. We found that the probability to copy tit preference decreased with decreasing learning performance in females, particularly yearling ones: fast learning females copied tit preference, while slow learning ones rejected it. Male learning performance did not affect copying behavior. Our results showed that learning performance might play an important role in the ability to optimally use information for nest site selection in females: both fast and slow learning females could process this heterospecific information source but used it differently. This could partly explain the link between cognitive abilities and reproductive success reported in previous studies. Whether cognitive abilities may modulate condition-dependent costs of using different information remains to be explored.